Two consecutive lapses in participation in a weekend exercise program may lessen the benefit of the intervention for hyperglycemia - Kazuko Ishikawa-Takata; Toshiki Ohta (Japanese Society of Physical Fitness and Sports Medicine, 2017)
Recent studies have suggested that the amounts of both moderate to vigorous physical activity and sedentary behavior affect the incidence of type 2 diabetes. Recommendations regarding frequency of aerobic exercise training for persons with type 2 diabetes are to not allow more than 2 consecutive days without aerobic physical activity. This study reanalyzed the data from a Risk Factor Intervention Trial in Japan to examine whether a lack of participation in the exercise program on weekends lessened the benefit of the exercise intervention in hyperglycemia. Thirty-two participants with fasting serum glucose above 126 mg/dl at baseline or with a diagnosis of type 2 diabetes were selected from the original dataset. They had joined an aerobic exercise program at a fitness club for 8 weeks, and serum glucose was measured before and after the intervention. Participants who exercised once or more per week on the weekends (Saturday and/or Sunday) along with their weekday routine showed a significant decrease in serum glucose; and changes in serum glucose were smaller in those who participated less often. Adjustment for baseline serum glucose, undergoing diagnosis, total exercise time and changes in energy intake and body weight did not alter this result. It was shown that in exercise interventions for people with hyperglycemia, recommendations on the maximum sedentary interval, in addition to the minimum duration of exercise, should be considered.